The Moderating Effect of the COVID-19 Pandemic on the Human Capital Characteristics of Health and Education Expenditures - Sarıgül, Seval Selvi; Konca, Murat (Fırat University, 2024)
This study aimed to contribute to the literature by revealing whether the New Coronavirus (SARS-CoV-2, COVID-19) had a moderating effect on the effect of health and education expenditures on gross domestic product (GDP). In this context, in the analysis section of the study, a panel data set from 37 Organization for Economic Co-operation and Development (OECD) countries for the period 2015-2020 was used. Two models were established in the study. In Model I, the moderating effect of COVID-19 on the effect of health expenditures on GDP was examined. In Model II, the moderating effect of COVID-19 on the effect of education expenditures on GDP was examined. It was determined that health and education expenditures had a significant positive effect on GDP in both models (p0.05). Finally, no moderating effect of the COVID-19 was found on the effect of education and health expenditures on GDP (p>0.05).

Bu çalışmada sağlık ve eğitim harcamalarının gayri safi yurt içi hâsıla (GSYİH) üzerindeki etkisinde Yeni Koronavirüs (SARS-CoV-2, COVİD-19) değişkeninin moderatör etkisinin olup olmadığını ortaya koyarak literatüre katkıda bulunmak amaçlanmıştır. Bu kapsamda çalışmanın analiz kısmında 37 Ekonomik İşbirliği ve Kalkınma Örgütü (OECD) üyesi ülkenin 2015-2020 dönemine ait verileri ile oluşturulan panel veri seti kullanılmıştır. Çalışmada iki model kurulmuştur. Model I’de sağlık harcamalarının GSYİH üzerindeki etkisinde COVİD-19’un moderatör etkisi incelenmiştir. Model II’de ise, eğitim harcamalarının GSYİH üzerindeki etkisinde COVİD-19’un moderatör etkisi incelenmiştir. Her iki modelde de sağlık ve eğitim harcamalarının GSYİH üzerinde pozitif yönlü ve istatistiksel olarak anlamlı bir etkisinin olduğu tespit edilmiştir (p0,05). Son olarak, eğitim ve sağlık harcamalarının GSYİH üzerindeki etkisinde COVİD-19 değişkenin herhangi bir moderatör etkisi bulunamamıştır (p>0,05
SAĞLIK VE EĞİTİM HARCAMALARININ BEŞERİ SERMAYE ÖZELLİĞİ ÜZERİNDE COVİD-19 PANDEMİSİNİN MODERATÖR ETKİSİ
Keywords: Health Sciences Education and Development of Programs: Medicine; Nursing and Health Sciences; Sağlık Bilimleri Eğitimi ve Program Geliştirme: Tıp; Hemşirelik ve Sağlık Bilimleri